A ketogenic drink improves brain energy and some measures of cognition in mild cognitive impairment - Fortier, Mélanie; Castellano, Christian-Alexandre; Croteau, Etienne; Langlois, Francis; Bocti, Christian; St-Pierre, Valérie; Vandenberghe, Camille; Bernier, Michaël; Roy, Maggie; Descoteaux, Maxime; Whittingstall, Kevin; Lepage, Martin; et al. (Alzheimer's & dementia, 2019)
Unlike for glucose, uptake of the brain's main alternative fuel, ketones, remains normal in mild cognitive impairment (MCI). Ketogenic medium chain triglycerides (kMCTs) could improve cognition in MCI by providing the brain with more fuel. Fifty-two subjects with MCI were blindly randomized to 30 g/day of kMCT or matching placebo. Brain ketone and glucose metabolism (quantified by positron emission tomography; primary outcome) and cognitive performance (secondary outcome) were assessed at baseline and 6 months later. Brain ketone metabolism increased by 230% for subjects on the kMCT (P < .001) whereas brain glucose uptake remained unchanged. Measures of episodic memory, language, executive function, and processing speed improved on the kMCT versus baseline. Increased brain ketone uptake was positively related to several cognitive measures. Seventy-five percent of participants completed the intervention. A dose of 30 g/day of kMCT taken for 6 months bypasses a significant part of the brain glucose deficit and improves several cognitive outcomes in MCI. •30 g/day of medium chain triglyceride (kMCT) doubles brain ketone metabolism in MCI.•As a result, net brain energy status improved on the kMCT.•Improvement in some cognitive outcomes was positively related to brain ketone uptake.•Both the kMCT and placebo were moderately well tolerated.